KOMUNIKASI DAKWAH WAHDAH ISLAMIYAH DI SULAWESI SELATAN - Hadiati, Hadiati (Jurnal Komunikasi Islam, 2017)
This paper discusses the results of research empirically on dakwah communication of the group of Wahdah Islamiyah in South Sulawesi. There are two focus were discussed, namely; the communication strategy and communication networks of dakwah. The results indicate that; (1) The communication strategy was developed by strengthening the competency of preachers in terms of formulating material of dakwah, communication skills and strengthening the quality of their personality. The dakwah messages that formulated related to the problems facing the peoples, and the earnest efforts conducted to do not happen social cultural inequalities between the preachers with the people by sending the preachers whom coming from the communities which have the same social cultural background; (2) The communication network of dakwah on the macro level developed by collaborating with the institutions of Government and the non-formal institutions in the countries of the Middle East, so the dakwah movement supported morally and materially; (3) the communications network at the micro level developed by Wahdah Islamiyah with emphasis on strength of personal communication network through the program “one cadre get one cadre (sks)”